miR-135a Reduces Osteosarcoma Pulmonary Metastasis by Targeting Both BMI1 and KLF4 - Chen, Chenglong; Mao, Xingjia; Cheng, Caitong; Jiao, Yurui; Zhou, Yi; Ren, Tingting; Wu, Zhuangzhuang; Lv, Zhi; Sun, Xiaojuan; Guo, Wei (Frontiers in Oncology, 2021)
Because of the modest response rate after surgery and chemotherapy, treatment of osteosarcoma (OS) remains challenging due to tumor recurrence and metastasis. miR-135a has been reported to act as an anticarcinogenic regulator of several cancers. However, its expression and function in osteosarcoma remain largely unknown. Here, we reported that abridged miR-135a expression in OS cells and tissues, and its expression is inversely correlated with the expression of BMI1 and KLF4, which are described as oncogenes in several cancers. Ectopic expression of miR-135a inhibited cell invasion and expression of BMI1 and KLF4 in OS cells. In vivo investigation confirmed that miR-135a acts as a tumor suppressor in OS to inhibit tumor growth and lung metastasis in xenograft nude mice. BMI1 and KLF4 were revealed to be direct targets of miR-135a, and miR-135a had a similar effect as the combination of si-BMI1 and si-KLF4 on inhibiting tumor progression and the expression of BMI1 and KLF4 in vivo. Altogether, our results demonstrate that the targeting of BMI1/KLF4 with miR-135a may provide an applicable strategy for exploring novel therapeutic approaches for OS.